Hi guys,

I am using the code pasted below with the corresponding output:

syms X w t p

eq = X*cos(w*t – p)

eq =

X*cos(p – t*w)

The output is is reversed it should instead be X*cos(w*t – p). How would I change this?

Skip to content# MATLAB: Output of symoblic expression coming out incorrectly

equationsymbolic

Hi guys,

I am using the code pasted below with the corresponding output:

syms X w t p

eq = X*cos(w*t – p)

eq =

X*cos(p – t*w)

The output is is reversed it should instead be X*cos(w*t – p). How would I change this?

## Best Answer